Une gouvernance environnementale selon l’état ? Le conservatoire du littoral entre intérêt général et principe de proximité - Yann Gérard (VertigO)
At the time when more democratic decision-making progress is put forward - taking into account the complexity of territorial contexts together with the actors acting upon it – the environmental centralised policies led by nations have to be constantly adapted when they are not merely discredited. The French shoreline shows well how new forms of public action are developing, particularly as far as the protection of natural areas is concerned. ICZM illustrates quite well the new rules of public action, often typified in the word « governance ».In that scope, the modes of intervention of a state body such as the « Conservatoire du littoral » are particularly worth considering. Even if its action, focused on property purchase, embodies a priori the state’s authoritarian character as regards public action, analysis shows that innovating practices in that matter originate in the public organization. Both centralised and territorialised, the feature of its action makes it possible to characterize a « territorial governance » in accordance with the state.